Debt and development in Latin America - Kim, Kwan S., ed. (University of Notre Dame P. Notre DameUS, 1985)
Contains 8 papers which focus on structuralist perspectives of the Latin American crisis, its financial side, and long term strategies for structuralist adjustment. Gives historical analysis of the causes of an unstable growth pattern attributable to the structural characteristics of a dependent capitalist economy. Traces historical origins and evolution of recent external debt problems in Latin America examining their implications for indebted countries and reviewing their scope, composition and outlook. Discusses exchange rates and concludes that small open economies are vulnerable to instability of the world monetary system. Provides adjustment and industrial development strategies for small and large economies respectively.